A construção do olhar geográfico na educação básica: por um ensino de geografia situado em contextos significativos - Diego Martins da Cruz (2024)
Is it possible to develop strategic resources that allow students to exercise a perspective that enables them to identify, understand and operate with what is geographical in the reality that surrounds them? In order to answer this question, we sought to build understandings about the pedagogical knowledge of content related to Geography by observing the semantic behavior of classes taught by basic education teachers, from public and private schools in Belo Horizonte, MG. The objective was to investigate the role of context in the teaching and learning process and identify basic elements for geographic education that favors contextualized scientific learning. We sought to identify mechanisms that favor the construction of a geographic perspective on reality, based on a dialogue promoted by contributions from geographic science, cognition sciences and education sciences. To pursue the proposed objectives, a translation device was built to support the observation of the levels of contextuality and abstraction mobilized in some Geography teaching practices, in order to be able to trace the profile and semantic plan of these practices. This movement made it possible to reflect on more or less promising theoretical-methodological paths for building metacognitive skills and building geographic reasoning. The understanding was consolidated that the contribution of Geography to the scientific learning of basic education students involves teaching based on the epistemes specific to the geographic field, anchored in contexts that give them significance.